Changing Higher Education for a Changing World - Callender, Claire; Locke, William; Marginson, Simon (Bloomsbury Higher Education Research, 2020)
Published open access,Changing Higher Education for a Changing World draws on the outcomes of the cutting-edge research programmes of the UK-based Centre for Global Higher Education, the world's largest social science research centre focused on higher education and its future. In countries with incomes at European levels, the majority of all families now have connections to higher education, and there is widespread popular interest in how it can be made better. Together, the contributors sharply illuminate key issues of public and policy interest across the world: Do research universities make society more equal or more unequal? Are students graduating with too much debt? Who do we want to be attending universities? Will learning technologies will abolish the need for bricks-and-mortar higher education institutions? What can countries do to improve their scientific performance? How can comparative teaching assessment and research assessment become much more effective? The book explores higher education in the major higher education regions including China, Europe, the UK and the USA. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by Knowledge Unlatched.